2022
DOI: 10.1155/2022/1089434
|View full text |Cite
|
Sign up to set email alerts
|

FABP4 and I-FABP Levels in Pregnant Women Are Associated with Body Mass Index but Not Gestational Diabetes

Tamara Vorobjova,
Aili Tagoma,
Ija Talja
et al.

Abstract: Objectives. Gestational diabetes mellitus (GDM) is glucose intolerance detected initially during pregnancy. GDM poses an increased risk for the development of diabetes later in life. Fatty acid-binding protein 4 (FABP4) is a regulator of lipid metabolism and is associated with obesity, insulin resistance, and type 2 diabetes. Increased level of intestinal fatty acid-binding protein (I-FABP) may indicate impaired intestinal permeability, which may be an important contributor to the pathogenesis of type 1 diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Consistently, lines of evidence also revealed that serum FABP4 levels are positively associated with maternal BMI [ 28 ], especially in the subgroup with BMI surpassing 25 [ 29 ]. Moreover, maternal circulating FABP4 levels are also negatively associated with serum adiponectin levels, which is a metabolically beneficial hormone [ 29 ]. These findings underscore that elevated FABP4 levels are intricately linked to adiposity gain during pregnancy, thus suggesting that FABP4 levels could serve as a predictive indicator of the degree of maternal obesity.…”
Section: The Role Of Fabp4 On Pregnancy Healthmentioning
confidence: 55%
See 1 more Smart Citation
“…Consistently, lines of evidence also revealed that serum FABP4 levels are positively associated with maternal BMI [ 28 ], especially in the subgroup with BMI surpassing 25 [ 29 ]. Moreover, maternal circulating FABP4 levels are also negatively associated with serum adiponectin levels, which is a metabolically beneficial hormone [ 29 ]. These findings underscore that elevated FABP4 levels are intricately linked to adiposity gain during pregnancy, thus suggesting that FABP4 levels could serve as a predictive indicator of the degree of maternal obesity.…”
Section: The Role Of Fabp4 On Pregnancy Healthmentioning
confidence: 55%
“…Growing studies demonstrate that elevated circulating FABP4 levels correlate with an increased risk for obesity [ 24 ], type 2 diabetes [ 25 ], various cardiovascular diseases [ 26 ], and cancers [ 27 ] in a wide variety of populations. In pregnancy, increased serum FABP4 concentrations are observed in pregnant women with maternal obesity [ 28 , 29 ], GDM [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], and PE [ 28 , 40 , 41 , 42 ]. However, its expression is detected in human placental trophoblast cells and is dispensable for maternal–fetal exchange and fetal growth [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that FABP4 increased in circulation as BMI increased in women participating in the study and interestingly both A‐FABP and I‐FABP were related higher BMI. [ 28,42 ]…”
Section: Insulin Resistance and Diabetesmentioning
confidence: 99%
“…Previous studies by us and others showed increased circulating levels of FABP4 in women with GDM compared women with normal glucose tolerance (NGT) 26–30 . Yet, a causal link between increased FABP4 and the pathophysiology of GDM has not been shown, and it is unclear whether the increase in FABP4 is related to obesity or to the related metabolic abnormalities 31 …”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30] Yet, a causal link between increased FABP4 and the pathophysiology of GDM has not been shown, and it is unclear whether the increase in FABP4 is related to obesity or to the related metabolic abnormalities. 31 In this study, we aimed to determine the tissue origin of elevated circulating FABP4 levels in GDM and to assess its potential contribution in promoting hepatic glucose production. Using biopsies of placenta, subcutaneous and visceral white adipose tissues (sWAT and vWAT, respectively), we showed that FABP4 is secreted from these tissues during pregnancy, with an approximately two-fold increase in vWAT secretion observed in women with GDM compared with NGT.…”
Section: Introductionmentioning
confidence: 99%